Project Based Learning in an ESP Class: Voices from Indonesian EFL Students (Conference on English Language Teaching, 2023)
To adapt with the current era, students need to be encouraged to master various practical skills needed in the 21st century. Consequently, an interesting and student-centered learning model is needed to improve the quality of education and teaching, especially in the field of language education. In this regard, the application of the Project Based Learning can be the solution to support the effectiveness of language learning. Based on this issue, this case study aims to explore students’ perceptions of the implementation of Project based Learning in an ESP course. Semi-structured interview is employed as a data collection technique. The data obtained were analyzed thematically. This study revealed that students have a positive perception of the implementation of project-based learning as they considered it as an effective learning method which could promote their creativity, collaboration, and critical thinking skills. In addition, it can also support the development of their language skills. The results of this study are expected to provide an overview and serve as a consideration for language teachers to implement Project based Learning in their teaching practices.